The nexus of production diversity, market participation and dietary diversity: Insights from Ethiopia - Tigabu Degu Getahun; Gebeyehu Fetene (University of Bonn, Center for Development Research (ZEF), 2021)
This study examines the nexus among production diversity, market participation, and consumption diversity in smallholder households. It identifies the main factors that influence smallholder farm households' decision to diversify production and evaluates the effect of production diversity and market participation on consumption diversity. To this end, we use a three-wave panel data of 7110 households in rural Ethiopia. The estimation results from the Mundlak Fixed Effects instrumental method suggest that risk-averse households, households with larger cultivated land, households with larger family size and family labor, and households who participate in community meetings are more likely to diversify their production. The results further reveal that production diversity has a statistically significant and positive effect on the consumption diversity of household members, but not dietary diversity of children and women. We find that market integration is more relevant in improving nutrition than production diversity. These results suggest that policies that merely focus on encouraging smallholder farmers to diversify production would not be that effective unless they are coupled with interventions that aim to integrate smallholder farmers to the market.
Keywords: D40; Q13; Q18; E21; 330; production diversity; consumption (diet) diversity; risk preference; market participation; endogeneity